Ecological Restoration and Key Technologies in High-Diving Mining Areas - Zhang, Huifang (International Journal of Natural Resources and Environmental Studies, 2025)
Ecological management and environmental restoration of mines are the cornerstone of sustainable resource exploitation, and it is imperative to strengthen the ecological protection and restoration of mining areas. High-diving mining areas are often located in the hinterland of the plains, with high surface diving levels and proximity to urban areas, forming a unique ecosystem of land and water. Such mining areas are characterized by wide subsidence, widespread water accumulation, and challenging treatment technologies. Therefore, in view of the particularity of the high-diving mining area of Zhaogu No. 1 Mine, it is particularly important to adhere to the principle of "adapting measures to local conditions, agriculture if it is suitable for agriculture, fishing if it is suitable for fishing, and construction if it is suitable for construction". Through an in-depth analysis of the ecological and environmental problems exposed during the mining process of Zhaoguyi mine, we found that the mining area is currently facing six serious challenges: significant damage to the topography and landscape, extensive damage to natural vegetation, serious damage and illegal occupation of land resources, resulting in a sharp reduction in arable area, and unprecedented damage to the ground infrastructure. In order to solve the ecological and environmental problems left by Zhaogu No. 1 Mine, three core key technologies were studied: topography and landform remodeling technology, soil reconstruction and vegetation restoration technology, channel reengineering and road engineering technology. The synergy of these technical systems provides a comprehensive strategic planning and implementation plan for the geomorphological restoration, vegetation restoration and surface infrastructure reconstruction of the Zhaogu mining area. Through the on-site ecological restoration project of Zhaogu No. 1 Mine, this paper not only verifies the efficiency and applicability of the ecological restoration technology combined with specific terrain, ecological environment and surface facilities under the conditions of high diving mining area, but also highlights the great guiding significance of these research results for the ecological environment restoration work of Zhaogu No. 1 Mine and even similar mining areas, and sets a model for future ecological restoration practice.